Dynamic effects of monetary policy shocks on macroeconomic volatility - Haroon Mumtaz; Konstantinos Theodoridis (Queen Mary University of London, School of Economics and Finance, 2015)
We use a simple New Keynesian model, with firm specific capital, non-zero steady-state inflation, long-run risks and Epstein-Zin preferences to study the volatility implications of a monetary policy shock. An unexpected increases in the policy rate by 150 basis points causes output and inflation volatility to rise around 10% above their steady-state standard deviations. VAR based empirical results support the model implications that contractionary shocks increase volatility. The volatility effects of the shock are driven by agents' concern about the (in)ability of the monetary authority to reverse deviations from the policy rule and the results are re-enforced by the presence of non-zero trend inflation.
Keywords: E30; E40; E52; C11; C13; C15; C50; 330; DSGE; Non-linear SVAR; New Keynesian; Non-zero steady state inflation; Epstein-Zin preferences; Stochastic volatility